ISLAMIC BOARDING SCHOOLS AS AN EFFORT TO PREVENT RADICALISM BASED ON PROPHETIC (Case Study of Islamic Boarding Schools Madrasah Wathoniyah Islamiyah Banyumas) - Muhdir; Aldi Prasetyo (PROCEEDING AL GHAZALI International Conference, 2023)
Religion is the most influential factor in many phenomena of social conflict in society. An unbalanced understanding of religion is one of the triggers. Therefore, efforts are needed in educating the public about good religious behaviors so that people can understand that the existence of religion can create harmony in social life, not to cause hostility. Islamic boarding schools can be expected to be a way out to unravel religious issues into problems in Indonesia. Islamic boarding schools play a role in realizing peace in the lives of heterogeneous communities, namely through prophethood. The results in this study are Islamic boarding schools as an effort to prevent prophetic-based radicalism including first, hablun min Allah or the transcendent pillar of the spiritual bond between man and God. The pillar of Islamic boarding school humanization is trying to return to an education system that is not dependent on technology with the skills possessed by the students to improve intellectually. Activities in developing the inculcation of cultural values ​​and local wisdom owned by Islamic boarding schools.